A New Recognition on Modern Spinal Rehabilitation Medicine from Visual Angle of "Putting Tendon First" Theory - Xinmiao YAO; Guoqing ZHOU (康复学报)
Objective:To improve the identification of modern spinal rehabilitation medicine from the visual angle of"putting tendon first"theory, and combine the research achievements of integrated Traditional Chinese Medicine (TCM) therapy with modern rehabilitation medicine, in order to improve the comprehensive prevention and treatment ability of spinal disorders.Methods:The current situation of TCM conservative treatment for spinal disorders was analyzed, and the characteristics of integrated TCM therapy for prevention and treatment of spinal disorders was concluded.Results:The current domestic practitioners who engaged in the prevention and treatment of spinal disorders were lack of knowledge renewal of modern spinal rehabilitation medicine, and lack of systemic and persistent treatment for patients with spinal disorders.Conclusion:Advocating"putting tendon first"theory, paying attention to function and soft tissues balance, and combining the integrated TCM therapy with modern rehabilitation medicine are the key links of prevention and treatment of spinal disorders. It is a huge task to update knowledge of modern spinal rehabilitation medicine and improve the comprehensive prevention and treatment ability of spinal disorders.